The Use of English Children’s Song Media in Improving Students Pronounciation - Indi Rahmawati Salisah; Suryadi Suryadi; Jhon Pahamzah (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The purpose of this study was to determine how the influence of children's song media on improving English pronunciation skills of fourth grade students of MI Bina Ummat. This study has a single group pretest and posttest design and is experimental in nature. Thirty children from the fourth grade of MI Bina Ummat became the study population. The t test was used in the analysis of this research data. The findings of the study showed that the children's song media had an impact on students' English pronunciation, with t count 8.101 > t table 2.042, an average value of 54.00 for pre-test data and an average value of 80.64 for post-test data . The difference in the average value is 24.64 with a percentage of 42%. The results show how much the student's pronunciation ability changes. The use of children's song media has an impact on improving the English pronunciation skills of grade IV students at MI Bina Ummat, according to these findings.